MANAGEMENT OF ENDOCRINE DISEASE: Visual morbidity in patients with pituitary adenoma. Issue 5 (November 2019) - Lithgow, Kirstie; Batra, Ruchika; Matthews, Tim; Karavitaki, Niki
Abstract : Visual dysfunction is an important element in the morbidity encountered in patients with pituitary adenoma leading to functional impairment and compromised quality of life. It consists of many parameters (even in the absence of reported symptomatology) as a result of tumour growth in proximity to structures critical for vision (anterior visual pathway, cranial nerves within cavernous sinuses), and as an adverse consequence of therapeutic interventions. Adenoma resection leads to high rates of visual improvement and possibly continues beyond a year post surgery, but the exact timing of maximum effect requires elucidation. Retinal nerve fibre layer measurement may be a reliable, objective parameter predicting favourable visual outcomes, although its prognostic value when pathological, needs to be confirmed. For compromised vision after pituitary apoplexy, early surgical decompression remains usual practice until evidence-based guidance becomes available. The risk of radiation-induced visual toxicity is mainly influenced by total and per fraction dose of radiation and treatment modality. Careful selection of cases and of radiotherapy technique/planning are of major importance in minimising this risk. Dopamine agonists lead to visual recovery in a considerable number of prolactinoma patients. Visual morbidity should be considered a vital indicator in the metrics of quality of service/care in pituitary disease making regular, full ophthalmic examination an essential component of modern management of pituitary pathology at all time points of patient pathway. Well-designed studies minimising effects of bias and using tools and scoring systems reliably reflecting visual status will provide robust evidence on valid prognostication and patient stratification guiding clinical decision making.